2010
DOI: 10.9744/ing.v11i2.17887
|View full text |Cite
|
Sign up to set email alerts
|

Factors Inhibiting and Facilitating Japanese Teachers of English in Adopting Communicative Language Teaching Methodologies

Abstract: This is a partial report on junior and senior high school Japanese teachers of English and changes in their beliefs and practices after attending a 4-month program of language and pedagogical study in Canada. Findings from this case study suggest that this group of Japanese teachers could effectively apply what they had learned abroad if they were not bound by practical constraints, external influences, or if they were teaching specifically communication-oriented classes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 3 publications
(4 reference statements)
1
1
0
Order By: Relevance
“…These were: (a) a deficiency in the level of clarity and understanding of the innovation, (b) inadequate skills and knowledge necessary to implement innovation, (c) inadequate material resources, and (d) organisational provisions that were incompatible with implementation. Gross et al's work has been supported by findings in other international studies which have found concerns about workload, a lack of sufficient time to enact the curriculum, the expense of professional development and shortages in appropriate teaching materials as being related to implementation difficulties (see Carless, 2001;Cook, 2009;O'Donnell, 2005;Richards & Pennington, 1998;Sato & Kleinsasser, 2004;Waters & Vilches, 2008). Interestingly, in terms of organisational provisions, Sato and Kleinsasser's (2004) study of the beliefs, practices, and interactions of teachers in a Japanese high school English department found that peer planning and peer observation worked to reinforce the status quo rather than to question it or to stimulate change.…”
Section: The Role Of the Teacher In Curriculum Reformsupporting
confidence: 61%
“…These were: (a) a deficiency in the level of clarity and understanding of the innovation, (b) inadequate skills and knowledge necessary to implement innovation, (c) inadequate material resources, and (d) organisational provisions that were incompatible with implementation. Gross et al's work has been supported by findings in other international studies which have found concerns about workload, a lack of sufficient time to enact the curriculum, the expense of professional development and shortages in appropriate teaching materials as being related to implementation difficulties (see Carless, 2001;Cook, 2009;O'Donnell, 2005;Richards & Pennington, 1998;Sato & Kleinsasser, 2004;Waters & Vilches, 2008). Interestingly, in terms of organisational provisions, Sato and Kleinsasser's (2004) study of the beliefs, practices, and interactions of teachers in a Japanese high school English department found that peer planning and peer observation worked to reinforce the status quo rather than to question it or to stimulate change.…”
Section: The Role Of the Teacher In Curriculum Reformsupporting
confidence: 61%
“…Nonetheless, if this were so, the problem arises as to how to provide more curriculum time for such activities. Recalling the research referred to in the introduction to this paper (e.g., Cook, 2009;Gorsuch, 2001; O"Donnell, 2005), Japanese teachers have frequently cited lack of time and space in the curriculum as impediments working against their adoption of policy-oriented practices, such as speed reading. In the absence of any positive change in curriculum conditions, teachers would need to devise creative ways of integrating such instruction with current materials and content (see, for example, Underwood & Hattori, 2010, on ways to integrate speed reading with MEXT-approved textbooks).…”
Section: Discussionmentioning
confidence: 99%